Clinical study of Misgav Ladach technique of caesarean section - Gadappa, Shrinivas N.; Dixit, Pratibha V.; Sharma, Deepika; Gavit, Yogita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: In the last decades caesarean section rates increased in many countries becoming the most performed intraperitoneal surgical procedure. The operative technique performed is made chiefly on the basis of the individual experience and preference of operators, the characteristics of patients, timing and urgency of intervention. Present study was undertaken to assess the benefits of the Misgav Ladach caesarean section technique in tertiary care hospital and evaluate the operative parameters like efficacy, safety, duration of surgery, blood loss, need for suture material, post-operative morbidity. Methods: Prospective surgical interventional study conducted in department of obstetrics and gynecology in tertiary care institute. Results: The duration of surgery, blood loss and post-operative complications were significantly less in the Misgav Ladach technique of LSCS. Conclusions: The choice of the Caesarean section technique is strictly linked to the individual experience and confidence of the surgical team. Misgav-Ladach technique proved to be associated to less complications, moreover, since its shorter operating time; it is to prefer in all that cases a prompt operation is required.